PERAN GURU PENDIDIKAN ISLAM DAN TANTANGANNYA TERHADAP IDEOLOGI SEKULERISME - Jerri Gunandar; Najihah Binti Abdul Wahid (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2019)
Muslim teacher professionalism is very important agenda needs to be focused in order to develop a generation of pious and righteous human capital. However, the challenge of sekulerism will affect the noble intentions of teachers in building a pupil, characterized by the Quran. Therefore this paper will discuss the sekulerism ideology, the concept of a Muslim teacher, manifestation of sekulerism and sekulerism challenges confronting the Muslim teachers. This concept paper also touches on three main principles in relation to sekulerism which is fundamental to spoil the Muslims rational principles, the principle of openness and intellectual freedom. The future impact on education if this misunderstanding is not handled properly by the Muslim teachers, it will ruin the students generation who will shape the future of the country.